Comparison of two non-invasive arterial blood pressure monitoring techniques in brown bears (Ursus arctos). (June 2020) - Morelli, Jacopo; Briganti, Angela; Fuchs, Boris; Huber, Ðuro; Evans, Alina L.; Reljić, Slaven; Arnemo, Jon M.
Abstract: Monitoring arterial blood pressure (BP), represents a more accurate evaluation of hemodynamics than heart rate alone and is essential for preventing and treating intra- and post-operative complications in wildlife chemical immobilization. The objectives of the study were to test the correlation between standard oscillometry and Korotkoff's technique in anesthetized free-ranging brown bears in Croatia and Scandinavia and to assess the blood pressure in both locations. Five bears were snared and darted with xylazine and ketamine in Croatia, and 20 bears were darted from a helicopter with medetomidine and tiletamine-zolazepam in Scandinavia. Blood pressure was simultaneously measured with both techniques every 5 minutes. Correlation between techniques, trends of BP variation, and the factors of the capture which likely influenced BP were assessed. Successful measurements of BP were achieved in 93% of all attempts with the Korotkoff's technique but in only 29% of all attempts with oscillometry. The latter method mostly provided lower values of BP compared to Korotkoff's technique in yearlings. Most bears showed a decreasing trend in systolic and mean BP over time, consistent between the two techniques. All bears were hypertensive: the auscultatory technique detected moderate to severe systolic hypertension in 25% and 84% of bears in Croatia and in Scandinavia, respectively, with significantly higher BP in subadults and adults compared to yearlings. Only Korotkoff's method resulted in a reliable and effective tool for BP assessment in brown bears. The anesthetic protocols used in the present study in association with the capture methods produced hypertension in all animals.